INTERAKSI GENDER TOP MANAGEMENT DAN KONVERGENSI IFRS TERHADAP PRAKTIK EARNINGS MANAGEMENT PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010 – 2013 - Jeneffer Tirtadinata; Dedhy Sulistiawan (CALYPTRA, 2018)
Abstract –This research is to test whether adopting IFRS and the presence of women in top management will give a negative impact on earnings management, due to the differences in behaviour between men and women. The samples used in this study were that all business entities listed in Indonesia Stock Exchange for the periode 2010 – 2013. The samples used in this study are 324 companies. After testing, the obtained results indicate that the adoption of IFRS did not give a significant negative effect on earnings management on accrual and real basis. Concerning the presence women in top management, it does not have a negative significant influence on accrual earnings management; yet it provides a significant positive effect on real earnings management when measured using abnormal discretionary costs, and provide a significant negative effect on real earnings management when measured using abnormal production costs.